2023
DOI: 10.1038/s41377-023-01233-z
|View full text |Cite
|
Sign up to set email alerts
|

Robotic pendant drop: containerless liquid for μs-resolved, AI-executable XPCS

Doga Yamac Ozgulbas,
Don Jensen,
Rory Butler
et al.

Abstract: The dynamics and structure of mixed phases in a complex fluid can significantly impact its material properties, such as viscoelasticity. Small-angle X-ray Photon Correlation Spectroscopy (SA-XPCS) can probe the spontaneous spatial fluctuations of the mixed phases under various in situ environments over wide spatiotemporal ranges (10−6–103 s /10−10–10−6 m). Tailored material design, however, requires searching through a massive number of sample compositions and experimental parameters, which is beyond the bandw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
1
0
0
Order By: Relevance
“…Robotic pendant drop provides an end-to-end automated, μs-resolved XPCS workflow for studying the dynamics and structures of complex fluids. Ozgulbas et al 65 recently demonstrated that Brownian dynamics of nanoparticle colloid in a pendant drop is consistent with the reference setup such as thin-walled quartz capillaries. Furthermore, the pendant drop setup can be integrated with a robotic arm (UR3e) to fully automate sample preparation, characterization, and disposal.…”
Section: Example Applicationssupporting
confidence: 65%
“…Robotic pendant drop provides an end-to-end automated, μs-resolved XPCS workflow for studying the dynamics and structures of complex fluids. Ozgulbas et al 65 recently demonstrated that Brownian dynamics of nanoparticle colloid in a pendant drop is consistent with the reference setup such as thin-walled quartz capillaries. Furthermore, the pendant drop setup can be integrated with a robotic arm (UR3e) to fully automate sample preparation, characterization, and disposal.…”
Section: Example Applicationssupporting
confidence: 65%